EFEKTIVITAS PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) BIDANG PENDIDIKAN BANK INDONESIA TERHADAP PENGEMBANGAN SOFT SKILL MAHASISWA (Survei pada Kegiatan Mahasiswa GenBI Korkom Surabaya Madura-Bojonegoro 2023) - Novita Ariani, Shinta; Vinda Maya Setianingrum (The Commercium, 2025)
GenBI is a community of Bank Indonesia (BI) scholarship.This study aims to examine the impact of the effectiveness of the CSR program on the development of students' soft skills, specifically through the activities of GenBI students in 2023 in the Korkom Surabaya Madura-Bojonegoro region. The research approach is quantitative with a descriptive type. A total of 252 respondents and analyzed using simple linear regression analysis with a 95% confidence level. The results of hypothesis testing show a Sig. value of 0.000 < 0.05, meaning that H0 is rejected and Ha is accepted, indicating that there is an effect of CSR Program Effectiveness (X) on the Development of Students' Soft Skills (Y). The most effective program in terms of the number of respondents is the Sharia Economic Festival (FESYAR) with 107 respondents. On the other hand, the OKE Jatim Committee program, with 35 respondents, recorded the lowest number.